Penerapan Sustainable Living pada Rumah Tangga dengan Pembuatan Produk Kesehatan Ramah Lingkungan - Dyani Primasari Sukamdi; Mega Octavia; Muhammad Fariez Kurniawan; Pramitha Esha Nirmala Dewi; Inayati Murwani Rahayu (Jurnal Surya Masyarakat, 2022)
Public outrage over the Covid-19 pandemic has a detrimental effect on the habit of staying at home and contributes to increased household waste. The temporary closure of the TPTS Piyungan Yogyakarta has exacerbated the problem of garbage and household waste accumulation. Al Fatah Kindergarten, in collaboration with the School of Pharmacy Universitas Muhammadiyah Yogyakarta, wishes to encourage the community to practice environmental stewardship. The environmental conservation effort will begin at home with domestic waste management. This guidance tries to broaden the public's perception and understanding of waste. Online counseling and training are available on two primary topics: "Wise Waste Management Begining at Home" and "Making Soap and Candles from Waste Cooking Oil." "Wise to Manage Waste Beginning at Home" discusses how to separate waste and repurpose it starting with household waste. Meanwhile, "Making Soap and Candles from Used Cooking Oil" provides instruction on how to make simple soap and candles from used cooking oil, a common household waste. According to the questionnaires distributed to participants, some participants gained additional insight into how to incorporate sustainable living practices, particularly waste management, into their daily lives. Additionally, participants can comprehend the definition and practice of  garbage charity. As many as 94 percent of service users expressed satisfaction with their waste processing experience.